Foreign Policy Change: From Policy Adjustments to Fundamental Reorientations. (August 2021) - Haesebrouck, Tim; Joly, Jeroen
Over the last decades, an increasing number of empirical studies have examined foreign policy change. In this article, we provide an overview of different conceptualizations and understandings of foreign policy change, identify the different drivers and inhibitors of change, and suggest avenues for future research. Most importantly, this review argues that scholarship provides relevant insights in foreign policy change on specific issues, but currently fails to unravel cases of more fundamental change like, redirections of states' entire orientation toward world affairs or broader foreign policy categories (e.g. development aid or defense and security policy). Moreover, while the literature on foreign policy change has arrived at a list of plausible explanatory conditions for change, it has yet to provide a more general theoretical framework that captures the interplay between explanations from different levels of analysis in an integrated model. In consequence, we argue that research on foreign policy change would greatly benefit from comparative research that examines change in a more systematic way across countries, foreign policy domains, and over longer periods of time, with the goal of arriving at a more general explanatory model of foreign policy change.